Reducing Violent Crime and Firearms Violence in Indianapolis, Indiana, 2003-2005 - Chermak, Steven M. ([Verlag nicht ermittelbar], 2009)
The lever-pulling model was first developed as part of a broad-based, problem-solving effort implemented in Boston in the mid-1990s. The lever-pulling strategy was a foundational element of many collaborative partnerships across the country and it was a central element of the strategic plans of many Project Safe Neighborhoods (PSN) jurisdictions. This effort attempted to deter the future violent behavior of chronic offenders by first communicating directly to them about the impact that violence had on the community and the implementation of new efforts to respond to it, and then giving credibility to this communication effort by using all available legal sanctions (i.e., levers) against these offenders when violence occurred. The purpose of the study was to perform an experimental evaluation of a lever-pulling strategy implemented in Indianapolis, Indiana. Probationers were randomly assigned to the law enforcement focused lever-pulling group, the community leader lever-pulling group, or a regular probation control group during six months between June 2003 and March 2004. There were a total of 540 probationers in the study--180 probationers in each group. Probationers in the law enforcement focused lever-pulling group had face-to-face meetings with federal and local law enforcement officials and primarily received a deterrence-based message, but community officials also discussed various types of job and treatment opportunities. In contrast, probationers in the community leader lever-pulling group attended meetings with community leaders and service providers who exclusively focused on the impact of violence on the community and available services. Three types of data were collected to assess perceptions about the meeting: offending behavior, program participation behavior, and the levers pulled. First, data were collected using a self-report survey instrument (Part 1). Second, the complete criminal history for probationers (Part 2) was collected one-year after their meeting date. Third, all available probation data (Part 3) were collected 365 days after the meeting date. Part 1, Self-Report Survey Data, includes a total of 316 variables related to the following three types of data: Section I: meeting evaluation and perception of risk, Section II: Self-reported offense and gun use behavior, and Section III: Demographics. Part 2, Criminal History Data, includes a total of 94 variables collected about the probationer's complete offending history as well as their criminal activities after the treatment for one year. Part 3, Probation Data, includes a total of 249 variables related to probation history and other outcome data.